Voltage-dependent P/Q-type calcium channels at the frog neuromuscular junction - Nurullin, L. F; Mukhitov, A. R; Tsentsevytsky, A. N; Petrova, N. V; Samigullin, D. V; Malomouzh, A. I; Bukharaeva, E. A; Vyskočil, František; Nikolsky, E. E (Physiological research, 2011)
It is well known that antagonists of N-type voltage-gated calcium channels inhibit the evoked quantal release of acetylcholine in amphibian neuromuscular synapses. This, however, does not exclude the functional expression of other types of voltage-gated calcium channels in these nerve terminals. Using immunocytochemistry, we detected the expression of the α1A subunit of P/Q-type calcium channels (that is otherwise typical of mammalian motor nerve endings) in the frog neuromuscular junction. In addition, we demonstrated that the P/Q-type channel blocker ω-agatoxin IVA (20 nM) reduced the action potentialinduced calcium transient and significantly decreased both spontaneous and evoked mediator release. Our data indicates the functional expression of P/Q-type calcium channels in the frog motor nerve ending which participate in acetylcholine release.
Keywords: Synaptic Transmission; vápníková signalizace; nervosvalové spojení; Ion Channel Gating; zvířata; nervový přenos; Calcium Signaling; Animals; Rana ridibunda; Neuromuscular Junction; Membrane Potentials; vápník; gating iontového kanálu; Calcium; membránové potenciály